A new basal iguanodont (Dinosauria: Ornithischia) from the Wealden (Lower Cretaceous) of England - Mcdonald, Andrew T.; Barrett, Paul M.; Chapman, Sandra D. (Zootaxa, 2010)
A nearly complete right dentary originally noted by Mantell in 1848 is redescribed. The specimen, NHMUK 28660, was discovered in a quarry near Cuckfield, West Sussex, from the same formation as the original teeth of Iguanodon anglicus. Fresh examination reveals that NHMUK 28660 exhibits a single autapomorphy (a row of foramina extending from the ventral surface of the symphysis onto the lateral surface of the dentary) and a unique combination of characters that distinguish it from all other iguanodontian dentaries. In light of this and because I. anglicus is regarded as a nomen dubium to which additional material cannot be unambiguously referred, NHMUK 28660 is made the holotype of the new genus and species Kukufeldia tilgatensis.